Very Low Activated Factor VII and Reduced Factor VII Antigen in Familial Abetalipoproteinaemia - Miller, G. J.; Mitropoulos, K. A.; Nanjee, M. N.; Howarth, D. J.; Martin, J. C.; Esnouf, M. P.; Reeves, B. E. A.; Miller, N. E.; Cooper, J. A. (Thrombosis and Haemostasis, 1998)
Abetalipoproteinaemia is a rare disorder of apolipoprotein B metabolism associated with extremely low plasma concentrations of triglyce-ride. To discover whether the general positive association between factor VII and triglyceride levels extends to this condition, 5 patients were compared with 18 controls. All patients had a triglyceride below 100 μmol/l. Plasma unesterified fatty acid concentration was normal. Although factor IX activity was only slightly reduced (mean 88% standard) and factor IX antigen was normal, mean activated factor VII in patients was strikingly reduced to 34% of that in controls, a level similar to that found in haemophilia B. The patients’ mean factor VII activity and factor VII antigen were also significantly reduced to 54% and 63% of those in controls, respectively. Mean factor XI activity and tissue factor pathway inhibitor activity were reduced in patients to 70% and 75% of control values respectively, while factor XII, factor XI antigen, factor X, prothrombin and protein C were normal.